2022
DOI: 10.2147/tcrm.s349185
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Serum Levels of IL-22, IL-23, and IL-17 for Idiopathic Pulmonary Fibrosis Associated with Lung Cancer

Abstract: Background Correlations between idiopathic pulmonary fibrosis (IPF) and lung cancer have been discussed in many previous studies. In the present work, we evaluated the potential diagnostic value of serum levels of Th17 cell-related cytokines for the detection of lung cancer-associated IPF. Methods Fifty-six patients who had been diagnosed with lung cancer-associated IPF were enrolled, and 59 patients with lung cancer but without IPF were also enrolled, and 60 healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our findings may offer new support for preventing and managing lung tumor-associated IPF (idiopathic pulmonary fibrosis), which Zhang et al. first discovered to have higher levels of IL-22, IL-23, and IL-17 in the serum of patients with IPF ( 54 ). According to several recent studies, interleukin-33 has been linked to the advancement of lung cancer and can have opposing effects on the disease depending on the circumstances ( 3 ).…”
Section: Serum Cytokine Levels As Possible Immunotherapeutic Targetsmentioning
confidence: 58%
See 2 more Smart Citations
“…Our findings may offer new support for preventing and managing lung tumor-associated IPF (idiopathic pulmonary fibrosis), which Zhang et al. first discovered to have higher levels of IL-22, IL-23, and IL-17 in the serum of patients with IPF ( 54 ). According to several recent studies, interleukin-33 has been linked to the advancement of lung cancer and can have opposing effects on the disease depending on the circumstances ( 3 ).…”
Section: Serum Cytokine Levels As Possible Immunotherapeutic Targetsmentioning
confidence: 58%
“…In a bioinformatics study, a Novel investigation found that KLRK1 is a prognostic and diagnostic biomarker for lung cancer ( 54 ). A homodimeric lectin-like receptor, KLRK1, encodes NKG2D.…”
Section: Additional Factors As Prognostic Indicators For Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, in liver cancer, the poor prognosis of patients is more related to Th17 / IL-17 in the tumor microenvironment (44,45), and the crucial function of Th17 / IL-17 on aggravating liver disease and promoting inflammation has also been reported (46)(47)(48). Several studies have suggested that IL-22 plays a protective role in hepatocyte injury and is able to promote hepatocyte regeneration (49)(50)(51). Furthermore, the IL-22 receptor is highly expressed in hepatocytes, suggesting that the important effector cells of IL-22 are hepatocytes.…”
Section: Discussionmentioning
confidence: 99%